Odpowiedzi

2010-03-29T14:10:51+02:00
A)x+5=10
x=5

b)2x+3=15
2x=12
x=6

c)5x+13=23
5x=10
x=2

d)3x+11=41
3x=30
x=10

e)-x+2=8
-x=6
x=-6

f)-x+5=2
-x=-3
x=3

g)-2x-7=11
-2x=18
x=-9

h)-5x=-12
x=12/5
x=2⅔
1 5 1
2010-03-29T14:15:58+02:00
A) x+5=10/ -5
x=5

b)2x+3=15/ -3
2x= 12/ :2
x= 6

c) 5x+13=23/-13
5x= 10/ :5
x=2

d)3x+11=41/- 11
3x= 30/:3
x= 10

e)-x+2= 8/ -2
-x=6/ :(-1)
x=-6

f)-x+5= 2/ -5
-x= -3/:(-1)
x=3

g)-2x-7=11/ -7
-2x= 4/:(-2)
x= -2

h)-5x+=-12 <- nie rozumiem tego bo jest -5x + (nie powinno być plusa), ja to zrobie tak:
-5x=-12/ -(-5)
x= -7

chyba dobrzexD
1 5 1